(3GdChRGf hGdCcGjjds ((3LQLS GHf GdMcje jhMfG GdeJfjM s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje cJGH GdChRGf hGdCcGjjd CeG GdhRf agh YHGQI Yf eYGedI Hjf LhgQjf EeG eJLGfSjf Ch ZjQ eJLGfSjf, hGdeQGO HGdeLGfSI GdeSGhGI aj GdNaI hGdKbd hGddWGaI hGdcKGaI GdPgH hGdaVI hGdMOjO s
(3BNQgG (B:s
(3bGd GHf MLGL aj GdJdNjU(B: (3GdOQhb CQHYI CQWGd, agPG eG CQOfG Cf fPcQg ef CeQ GdChRGf hGdCcGjjd, hGddg CYde aj Pdc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B32 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(844) s
Keywords: (3GdWHs